2021
DOI: 10.3390/su14010056
|View full text |Cite
|
Sign up to set email alerts
|

Linking Man and Nature: Relictual Forest Coenosis with Laurus nobilis L. and Celtis australis L. in Antica Lavinium, Italy

Abstract: The Mediterranean basin has been a refugium for relict plant taxa and native laurophyllic forests. The Latium coasts and, especially, the Antica Lavinium site, host relict forest communities, whose natural importance is enriched by their cultural value. Here, we aim at investigating the ecological framework, cultural and historical values, and management over time, of relict communities that have Laurus nobilis and Celtis australis as their priority habitats. To achieve this, we performed vegetation surveys an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Pliny (HN XV.135) stated that the laurel was not permitted for "profane" uses, and setting it on fire at altars "for the propitiation of divinities" was strictly forbidden, because "...it is very evident that the laurel protests against such usage by crackling as it does in the fire, thus, in some way, giving expression to its abhorrence of such treatment." It is ascertained (Albani Rocchetti et al 2021) that woodlands were widespread in Latium in antiquity and that the laurel was an important element occurring in these forests. Here it assumed an important sacred meaning especially in the area of the Antica Lavinium site as well as in the lucus Loretae close to the Aventine hill in Rome.…”
Section: Discussionmentioning
confidence: 99%
“…Pliny (HN XV.135) stated that the laurel was not permitted for "profane" uses, and setting it on fire at altars "for the propitiation of divinities" was strictly forbidden, because "...it is very evident that the laurel protests against such usage by crackling as it does in the fire, thus, in some way, giving expression to its abhorrence of such treatment." It is ascertained (Albani Rocchetti et al 2021) that woodlands were widespread in Latium in antiquity and that the laurel was an important element occurring in these forests. Here it assumed an important sacred meaning especially in the area of the Antica Lavinium site as well as in the lucus Loretae close to the Aventine hill in Rome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, archaeological areas, being better protected from anthropogenic disturbance compared to other human-managed areas, have proven to be valuable refuges for biodiversity conservation [5,6,32,33]. The permanence of natural habitats and the floristic richness found in these areas is considerable, with the occurrence of a high number of species of conservation interest [6,32,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in addition to the important role of maintaining the natural vegetation cover in such areas, previous studies have also shown that archaeological sites can provide refuges for plant and animal species, protecting them from human impact and stresses associated with urban development and thus helping to conserve their levels of biodiversity [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Indeed, cultural heritage management activity provides some protection for natural heritage compared to other highly disturbed human ecosystems.…”
Section: Introductionmentioning
confidence: 99%